Status Hak Ulayat Masyarakat Hukum Adat Yang Termasuk Dalam Kawasan Hutan Lindung (Kasus Desa Balung Kecamatan XIII Koto Kampar Kabupaten Kampar) - Rahman, Fadli; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
State shall recognize and respect the customary law community unit along with the rights traditional all still alive and in accordance with the development and principles of the Unitary Republic of Indonesia, as mandated in the Constitution of 1945. However, its implementation in the field lead to conflicts in the determination of forest areas by the central government unilaterally without the involvement of regional governments and local Indigenous stakeholders. Customary land rights of indigenous people's been inhabited for generations before the formation of the Unitary Republic of Indonesia, not necessarily become a forest area designated the Central Government through the Ministry of Environment and Forestry.On the basis of these problems the author interested in conducting research in the village of Kampar Regency Balung research objectives: a) To know the process of establishing a forest area by Central Government: b) To determine the existence of customary rights and traditional values Balung Village Community; c) To know the efforts Kampar District Government and Stakeholder Desa Adat Balung in freeing the traditional communal land from forest areas. This study is sociological, with descriptive qualitative approach, using methods of data collection: documentation, interviews, observation. Determination of respondents using probability sampling methods with interactive data analysis techniques (Huberman and Miles).The conclusion of the study: a) Determination of forest areas in Riau Province including the forest area in the village of Balung without reviewing directly to the site without involving regional and local government and community Kampar customary law; b) The existence of indigenous peoples and indigenous land rights Balung village is alive, growing and is still revered by members of indigenous communities Balung village; c)There are no Government's efforts Kampar and Nenek Mamak Stakeholder Indigenous Village Balung,and LAK(Lembaga Adat Kampar),NGOs (nongovernmental organizations) to propose changes in the forest area of the rights of indigenous land Desa Balung who entered the forest area defined by Central government. Suggestions results of research: a) required a serious effort on the government Kampar revise regional regulations exist which provide reinforcement where the rights of customary rights of indigenous peoples; b) the Central Government in setting forest area demanded from the field see the real conditions of existence of society and society customary law and Nenek Mamak involving Indigenous Stakeholders; c) Indigenous and Tribal Peoples have the right to sue the government to defend the rights of indigenous land.Keywords: Forest Zone, Indigenous Peoples, Land Rights